Fabrication and characterization of Ag2CO3/SnS2 composites with enhanced visible-light photocatalytic activity for the degradation of organic pollutants. Issue 105 (13th October 2015) - Luo, Jin; Zhou, Xiaosong; Zhang, Jinquan; Du, Zhihua
Abstract : The efficient charge transfer at the interfaces of the Ag2 CO3 /SnS2 composite due to the inner established electric field ( E ), which effectively facilitated interfacial charge transfer and improved photogenerated electron–hole pairs separation. Abstract : Ag2 CO3 /SnS2 composite photocatalysts with different Ag2 CO3 contents were fabricated by a facile and efficient chemical precipitation method. The as-prepared samples were characterized by scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, UV-Vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. The Ag2 CO3 /SnS2 photocatalyst displayed enhanced photocatalytic activity for the photocatalytic degradation of methyl orange (MO) under visible light irradiation ( λ > 420 nm), and the optimum rate constant of Ag2 CO3 /SnS2 at a weight content of 2.0% Ag2 CO3 for the degradation of MO was 6.22 and 1.65 times as high as that of pure Ag2 CO3 and SnS2, respectively. Such an enhanced photocatalytic performance was predominantly ascribed to the synergistic effect between Ag2 CO3 and SnS2, which effectively facilitated interfacial charge transfer and improved photogenerated electron–hole pair separation efficiency. Furthermore, the superoxide radical anions (˙O2 − ) and holes (h + ) were considered as the main reactive species during the photodegradation process, and a synergistic photocatalysis mechanism between Ag2 CO3 and SnS2 was proposed based on the experimental results.